Research on changes of speed frequency and stroke of each 10m in 50m freestyle swimming - Zhong, Y.; Liu, X. -L. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The average speed of each on stage of the top 8 players in the final of made 50m freestyle swimming tends to decline and the declination difference is remarkable(P<0.05) with the race going on. The swimming speed depends mainly on the stroke frequency and stroke range. In this research, the stroke frequency and stroke range of the players tend to decline, too. The declination of the stroke frequency has remarkable difference(P<0.05), while that of the stroke range has not though it tends to decline(P>0.05). This shows that the main reason of affecting swimming race declination is the stroke frequency of the players rather than their stroke range. It is, in this research, believed that the speed declination in the swimming race is mainly caused by the declination of their stroke frequency.